2010
DOI: 10.2139/ssrn.870498
|View full text |Cite
|
Sign up to set email alerts
|

Market Madness? The Case of Mad Money

Abstract: We study the market's reaction to Jim Cramer's recommendations on the television show Mad Money. Average abnormal overnight returns following his recommendations are over 3% for the entire sample, and 6.7% for stocks in the smallest quintile. Using a novel dataset of television viewership, we find that the price response is increasing in the number of wealthy viewers who watch the show but unaffected by the number of low income households viewing the recommendations. Consistent with theories of limits to arbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 41 publications
7
54
0
Order By: Relevance
“…Barber and Odean (2013) argue that poor performance of individual investors can coexist with short-term positive return effects because individuals hold stocks for longer than the duration of the positive returns, so they are negatively affected by the long-term return reversals documented in Barber et al (2009b). However, Kelley and Tetlock (2013) find no long-term return reversals in their data.When selecting investments to buy, individuals favor stocks that have experienced high past returns (Barber et al, 2009b)-consistent with survey evidence that, on average, they have extrapolative beliefs (De Bondt, 1993;Fisher and Statman, 2000;Vissing-Jørgensen, 2004;Greenwood and Shleifer, 2014;Choi and Robertson, 2017)-or recent attention-grabbing events such as abnormally high trading volume, an extreme return, news coverage, or advertising (Seasholes and Wu, 2007;Barber and Odean, 2008;Engelberg and Parsons, 2011;Engelberg et al, 2012;Lou, 2014). Individuals also tend to sell stocks with high past returns, so that they are net sellers of stocks with high returns over the past quarter and net buyers of stocks with high returns in the more distant past Keloharju, 2000, 2001b;Griffin et al, 2003;Jackson, 2003;Kaniel et al, 2008;Barber et al, 2009b).…”
supporting
confidence: 52%
“…Barber and Odean (2013) argue that poor performance of individual investors can coexist with short-term positive return effects because individuals hold stocks for longer than the duration of the positive returns, so they are negatively affected by the long-term return reversals documented in Barber et al (2009b). However, Kelley and Tetlock (2013) find no long-term return reversals in their data.When selecting investments to buy, individuals favor stocks that have experienced high past returns (Barber et al, 2009b)-consistent with survey evidence that, on average, they have extrapolative beliefs (De Bondt, 1993;Fisher and Statman, 2000;Vissing-Jørgensen, 2004;Greenwood and Shleifer, 2014;Choi and Robertson, 2017)-or recent attention-grabbing events such as abnormally high trading volume, an extreme return, news coverage, or advertising (Seasholes and Wu, 2007;Barber and Odean, 2008;Engelberg and Parsons, 2011;Engelberg et al, 2012;Lou, 2014). Individuals also tend to sell stocks with high past returns, so that they are net sellers of stocks with high returns over the past quarter and net buyers of stocks with high returns in the more distant past Keloharju, 2000, 2001b;Griffin et al, 2003;Jackson, 2003;Kaniel et al, 2008;Barber et al, 2009b).…”
supporting
confidence: 52%
“…Hence, Klibanoff et al (1998) contended that media coverage could accelerate investors' response. Engelberg et al (2012) examined the direct measurement indicator of investors' attention with Nielson's survey data. They found that when audience ratings were high, the inter-day return could attain the peak; when sell-out was suggested on a program, the weak price effect would show up; when concurrently considering the suggestion of both buy-in and sell-out.…”
Section: Relationship Between Media Coverage and Stock Pricesmentioning
confidence: 99%
“…Moreover, Tetlock et al (2008) also considered media coverage an important qualitative variable to capture the part difficult to be quantified through a company's fundamentals, especially the tendency that stock prices might underreact to the message implied negative meaning. According to Engelberg et al (2012), higher audience ratings could result in higher inter-day returns. However, if investors are recommended to adopt a sell-out strategy, it will lead to a weak price effect.…”
Section: Introductionmentioning
confidence: 99%
“…Massa and Simonov (2006) show that "home" and "industry" bias in stock ownership is likely based on familiarity -a cheap source of information. Engelberg, Sasseville, and Williams (2012) find that stocks recommended by Jim Cramer on his popular television show Mad Money appreciate the following day, presumably because viewers believe his stock picks contain useful information. Barber and Odean (2000a) show that individual investors are more likely to purchase attention-grabbing stocks, likely as a means of reducing the informational burden associated with stock picking.…”
Section: Introductionmentioning
confidence: 99%